Determination of radical scavenging activity of murraya koenigii and carica papaya. - Muhammad Shakir Abdul Aziz (2015)
Lately in this era, medicinal plants are widely used locally as well as widely in the world as folk medicine for several purposes. They have been used as antibacterial, antioxidant, antiulcer, anti-inflammatory, antiviral, anticancer agents and for the treatment and prevention of different types of illnesses, especially in developing countries. Several potential and generally known as useful plants were selected in the study of Radical Scavenging Activity. Therefore to obtain a scientific prove, these plants were evaluate under certain selected parameters by using in-vitro approach. First method is 2-Diphenyl- 1-Picrylhydrazyl ( DPPH) Radical scavenging Acitivity, and Ferric Ion Reduction assay method and ABTS Radical Cation Method. For the tests, the leaf and root of Murraya Koenigii and the leaf and branch of Carica papaya was done in the this study. The results were translated in this study as percentage of radical scavenging activity. From the experimental result, it was found that at concentration 300 μgml-1, all samples shown that highest radical scavenging activity compared to other concentrations.